Loop-mediated Isothermal Amplification (LAMP): Potato virus detection CIP – SOPXXX, v.1.1. - Fuentes, S. (International Potato Center, 2022)
This standard operational procedure (SOP) for LAMP testing covers the steps on how to use a field-deployable LAMP assay in the diagnosis of the major viruses infecting potato worldwide: Potato leaf roll virus (PLRV), Potato virus Y (PVY), and Potato virus X (PVX). It includes different steps from collecting samples, processing of them for nucleic acid extraction, preparing LAMP reaction, setting the Genie instrument, and recording of results. LAMP test can be rapidly adopted to detect different pathogens in different plants by just replacing the specific primers (for those pathogens) in the reaction, which makes it broadly applicable and adjustable to new pathogens.